(untitled) (FULafia Journal of Science and Technology, 2026)
This study presents an integrated geotechnical characterization of subsurface soils in Gandu, Lafia, north-central Nigeria, to evaluate their suitability for foundation support. Laboratory analysis (particle size distribution (PSD) and Atterberg limits) and in-situ test (standard penetration test (SPT)) were conducted on five (5) test pits (PT1-PT5). The PSD results show that the soils are predominantly fine-grained, with coefficients of uniformity (≈ 2.7–2.9) and curvature (≈ 0.8–0.9) suggesting uniformly graded fine soils and poor gradation. Atterberg limits analysis exhibited Liquid Limit (LL) of 28.7 – 35.0 %, Plastic Limit (PL) of 12.9 –24.8 %, and resultant plasticity indices (PI) of 7.7 – 22.1 %. Casagrande plasticity chart classification placed PT1 within the CL zone (clay of low plasticity) and PT2–PT5 in the ML–CL region (silty clay or clayey silt). The SPT N-values indicate an increase in stiffness with depth, signifying the effect of natural consolidation and overburden pressure. Soils with high PI exhibited lower penetration resistance, thereby establishing a clear relationship between plasticity and strength. Strong agreement was observed among PSD, Atterberg limits, and SPT results, which confirms the suitability of the combined index and in-situ testing for soil characterization and preliminary engineering assessment. Overall, the subsurface soils are characterized by moderate strength, low permeability, and moderate compressibility, making them suitable for lightly loaded structures with a well-designed foundation. However, if high-rise or heavier structures are desired, ground improvement or deep foundation systems may be required.